Daily Energy Intake from Meals and Afternoon Snacks: Findings from the Malaysian Adults Nutrition Survey(MANS) - Mohd Shariff, Zalilah; K., Mirnalini; Mohd Yusof, Safiah; A., Tahir; M. D., Siti Haslinda; D., Siti Rohana; M. Y., Khairul Zarina; S., Mohd Hasyami; H., Normah; A., Siti Fatimah (Nutrition Society of Malaysia, 2008)
Meal and snack patterns are associated with energy and nutrient intakes and consequently health and nutritional status. The aim of this paper is to describe the percentage of daily energy intake from meals and afternoon snack among Malaysian adults. The study included a representative sample of adults aged 18- 59 years (n=7349) from a nationwide Food Consumption Survey conducted by the Ministry of Health. Information on dietary intake was obtained using a one day 24-hour diet recall (24-HDR). Dietary data on 6886 adults were analysed using Nutritionist ProTM and statistical analysis was carried out using the SPSS 13.0. The median percentage of daily energy intake is reported only for adults consuming meals and afternoon tea and by socio-demographic characteristics as well as body mass index (BMI) status. More than 80% of Malaysian adults consumed morning meals, lunch and dinner and 54% reported having afternoon tea. The median percentage of energy intake from morning meals, lunch, dinner and afternoon tea was 29.9%, 30.5%, 32.4% and 17%, respectively. There were variations in the median percentage of energy from meals and snacks according to the socio-demographic variables and BMI status. It is important to understand the eating patterns of Malaysians as the information can assist in efforts to address obesity and diet-related chronic diseases among adults.